Randomised phase II trial of gemcitabine and nab-paclitaxel with necuparanib or placebo in untreated metastatic pancreas ductal adenocarcinoma. (June 2020) - O'Reilly, Eileen M.; Barone, Diletta; Mahalingam, Devalingam; Bekaii-Saab, Tanios; Shao, Spencer H.; Wolf, Julie; Rosano, Molly; Krause, Silva; Richards, Donald A.; Yu, Kenneth H.; Roach, James M.; Flaherty, Keith T.; et al.
Abstract: Background: Necuparanib, a rationally engineered low-molecular-weight heparin, combined with gemcitabine/nab-paclitaxel showed an encouraging safety and oncologic signal in a phase Ib trial. This randomised multicentre phase II trial evaluates the addition of necuparanib or placebo to gemcitabine/nab-paclitaxel in untreated metastatic pancreatic ductal adenocarcinoma (PDAC). Patients and methods: Eligibility included 18 years, histologically or cytologically confirmed metastatic PDAC, measurable disease and Eastern Co-Operative Oncology Group performance status of 0–1. Patients were randomly assigned to necuparanib (5 mg/kg subcutaneous injection once daily) or placebo (subcutaneous injection once daily) and gemcitabine/nab-paclitaxel on days 1, 8 and 15 of 28-day cycles. The primary end-point was median overall survival (OS), and secondary end-points included median progression-free survival, response rates and safety. Results: One-hundred ten patients were randomised, 62 to necuparanib arm and 58 to placebo arm. The futility boundary was crossed at a planned interim analysis, and the study was terminated by the Data Safety Monitoring Board. The median OS was 10.71 months (95% confidence interval [CI]: 7.95–11.96) for necuparanib arm and 9.99 months (95% CI: 7.85–12.85) for placebo arm (hazard ratio: 1.12, 95% CI: 0.66–1.89, P-value: 0.671). The necuparanib arm had a higher incidence of haematologic toxicity relative to placebo patients (83% and 70%). Conclusion: The addition of necuparanib to standard of care treatment for advanced PDAC did not improve OS. Safety was acceptable. No further development of necuparanib is planned although targeting the coagulation cascade pathway remains relevant in PDAC. NCT01621243 Highlights: Preclinical data have shown that necuparanib decreases tumour growth and metastatic spread in pancreas models. Early phase Ib evaluation of gemcitabine, nab-paclitaxel and necuparanib indicated safety for the combination and promising clinical activity. The addition of necuparanib to gemcitabine and nab-paclitaxel did not improve outcome over standard therapy.